As propriedades magnéticas no ensino fundamental I e II com o uso do lúdico e da descoberta como facilitadores da aprendizagem - Santos, Antonio Pereira dos (Universidade Estadual de Ponta Grossa (UEPG), 2026)
This paper presents the development, application, and analysis of the Educational Product – A Journey Toward the Magnetic Properties of Materials – aimed at teaching the concepts of magnetic fields and the magnetic properties of materials to Elementary School students. The guiding question of the work was: is it possible to honestly address concepts of magnetism in Elementary School (initial and final yaers) through playful activities and Bruner's discovery? We hypothesize that teaching strategies based on playfulness and inquiry promote greater student engagement and encourage the active and enjoyable development of scientific concepts. Our proposal is based on discovery learning, mainly the spiral curriculum model, adopting play as a teaching strategy to make Physics teaching more accessible and engaging. The Educational Product was implemented in multi-grade classes linked to a social assistance project in the city of Curitiba, Paraná, which serves children in socially vulnerable situations. The structure of the educational product included a unit plan divided into four phases, totaling nine lessons, question forms, accessible experiments, and a game—Magnetic Treasure Hunt—as the pinnacle of the learning process. The activities were planned considering the different forms of representation linked to playfulness in the context of Elementary School. The heterogeneity of the classes allowed us to identify these representations and analyze the interactions between students in the processes of investigation and problem-solving. During the implementation, we observed an evolution in the students' conceptual vocabulary, which began to use terms such as "magnetic field" and "magnetic force" instead of intuitive or informal explanations. The game allowed us to playfully assess the level of understanding of the content, revealing evidence of effective power and economy. The results analyzed throughout this dissertation indicate that the use of playful and experimental activities favors the construction of scientific knowledge, respecting the phases of students' cognitive development and enhancing learning through discovery. This study contributed to Physics teaching in basic education for presenting innovative methodological alternatives, especially in contexts with limited infrastructure. It also reinforced the importance of inquiry-based learning mediated by playful strategies.
Keywords: Aprendizagem por descoberta; Currículo em espiral; Ludicidade; Magnetismo; Ensino de física